Pengembangan Buku Ajar Assesment Pendidikan Berbasis Kontektstual Pada Mahasiswa Pendidikan Bahasa dan Sastra Indonesia IKIP Budi Utomo Malang - Lis Susilawati; Endang Setyowati (IKIP Budi Utomo Malang, 2022)
The purpose of this research is to create a context-based textbook on educational assessment. As for the type of research, development research based on the Borg-Gor model is adopted. The research was conducted in his three phases: development, validation, and textbook review. Data collection techniques were performed through documentation, questionnaires, observation sheets, and tests. Based on the research conducted, contextually developed educational assessment textbooks were found to be valid, practical and effective to use in the learning process. Textbooks on contextual educational assessment were validated with 84.3% ratings by linguists and 89.3% ratings by material experts. In addition, the response rate of the evaluation questionnaire from the students of the third examination is 96.7%, and it can be said that the practicality is also high. In addition, it was declared that textbooks would be used effectively in the learning process. This is evident from the fact that 79.8% of observation sheets were used in the previous trial.